TIME MATCHING OF WORK OF OIL POOL AND WELL UNDER A GAS-LIFT FLOWING DURING WELL PLANNING AND OPERATION - Бойко, Василь Степанович; Міщук, Богдан Михайлович; Веклин, Тарас Сергійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Joint and interdependent operation of flowing well and oil pool in the mode of dissolved gas, which allows to calculate the time change of minimum bottom-hole pressure was investigated. Methodology for calculating the conditions of joint operation of oil pool and flowing well based on solution of equations of fluid filtration in the layer and traffic flow in the well bore was investigated and proposed. Modes of coordinated and uncoordinated work of these two units, as well as steady and uneven operation which must be considered during the design and operation of wells were highlighted.